IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH VIDEO MAKING - Winda Syafitri (Universitas Potensi Utama, 2018)
English class is one of main sources of students to learn English as a second language in Indonesia. There might be a problem in English language teaching. This study aims at solving the low achievement of students’ speaking ability in University of Potensi Utama through video making activity. It applied Classroom Action Research (CAR) as the research design. The subject of this research was SI (System Information)-B day class who was sitting in the first semester which consisted of 24 students. The research was conducted in two cycles. The instrument for collecting the data were speaking test, observation sheet, and questionnaire sheet. Based on the analysis, students’ speaking achievement is improved in every test which are pre-test (61.7), post-test in cycle I (68.80) and post-test in cycle II (80.1). Based on the observation sheet and questionnaires, it was found that the teaching learning process ran well and the students were more active, motivated and enthusiastic. It was concluded that making video activity can improve the students’ speaking achievement.